Turizem in blaženje podnebnih sprememb: Oblikovanje modela ocene ogljičnega odtisa turistov, ki prenočijo v Sloveniji, in priporočil za zmanjševanje ogljičnega odtisa v slovenskem turizmu - Turnšek, Maja; Pogačar, Tjaša (2024)
Tourism and Climate Change Mitigation: Development of a Model for Assessing the Carbon Footprint of Tourists Staying in Slovenia and Recommendations for Reducing Carbon Footprint in Slovenian Tourism. The present monograph is the result of the project "CRP V7-2128 Climate Change and Sustainable Tourism Development in Slovenia". It is a targeted research project aimed at formulating strategic proposals for reducing the carbon footprint of Slovenian tourism and adapting it to climate change based on actual data and an in-depth model that includes the specifics of data collection on tourism in Slovenia. The monograph presents results that address the following project objectives: 1. Formulating and testing a model for assessing the carbon footprint of tourists staying in Slovenia, at the destination level, with initial results provided; 2. Formulating strategic recommendations at the national, municipal, and public and private provider levels with measures aimed at monitoring and reducing the carbon footprint of Slovenian tourism. The results address the achievement of the goals of the Paris Climate Agreement, the European Green Directive, the Slovenia 2030 Strategy, the Recovery and Resilience Plan, and the Strategy for Sustainable Development of Slovenian Tourism 2022-2028. The final recommendations contribute to the sustainable development of the Slovenian tourism and the consolidation of Slovenia as a green destination.
Keywords: tourism; climate change; carbon footprint; climate change mitigation measures; transportation; accommodation; experiences; tourist food consumption